2020
DOI: 10.1002/biot.202000048
|View full text |Cite
|
Sign up to set email alerts
|

Dissolvable Gelatin‐Based Microcarriers Generated through Droplet Microfluidics for Expansion and Culture of Mesenchymal Stromal Cells

Abstract: Microcarriers are synthetic particles used in bioreactor‐based cell manufacturing of anchorage‐dependent cells to promote proliferation at efficient physical volumes, mainly by increasing the surface area‐to‐volume ratio. Mesenchymal stromal cells (MSCs) are adherent cells that are used for numerous clinical trials of autologous and allogeneic cell therapy, thus requiring avenues for large‐scale cell production at efficiently low volumes and cost. Here, a dissolvable gelatin‐based microcarrier is developed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Recently, Ng et al reported a single‐channel droplet‐fluidics device with the capacity to generate 180 μm diameter genipin‐crosslinked gelatin spheres. 49 The rate of sphere production in the Ng study required 10 hours of run time to supply a 100 mL culture which is 50 times slower than what was achieved with our 100 channel system. Furthermore, genipin crosslinking of gelatin took 2 days to complete compared with seconds for photocrosslinking GelMA.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, Ng et al reported a single‐channel droplet‐fluidics device with the capacity to generate 180 μm diameter genipin‐crosslinked gelatin spheres. 49 The rate of sphere production in the Ng study required 10 hours of run time to supply a 100 mL culture which is 50 times slower than what was achieved with our 100 channel system. Furthermore, genipin crosslinking of gelatin took 2 days to complete compared with seconds for photocrosslinking GelMA.…”
Section: Discussionmentioning
confidence: 84%
“…The biodegradability of gelatin microcarriers can be achieved by collagenase. For instance, Ng et al fabricated dissolvable gelatin-based microcarriers for MSC expansion [ 176 ]. Another study showed that the gelatin microcarriers could enhance the efficiency of chondrogenesis in bone marrow stromal cells (BMSCs) in vitro [ 177 ].…”
Section: Appropriate Materials For Microcarriers In Cartilage Tementioning
confidence: 99%
“…Methods where the detachment efficiency and cell viability were greater than 90% were considered “Best,” whereas results in the range of 60%−90% were considered “Moderate,” and less than 60% were deemed “Inadequate.” Furthermore, the scalability of the responsive microcarrier detachment process was also assessed as it is significantly different from scaling up traditional enzymatic detachment methods. For methods implemented on a production scale (>1 L), they were considered “Best,” and small‐scale implementation (<1 L) was considered “Inadequate” (Dosta et al, 2020; Hanga et al, 2020; C. Li et al, 2016; Narumi et al, 2020; Ng et al, 2021; Yan et al, 2020; Yang et al, 2010; Yuan et al, 2018).…”
Section: Harvesting: Detachment Of Cells From Microcarriersmentioning
confidence: 99%
“…In this case, the primary target of the enzymes is the cleavage of microcarriers rather than cellular membrane proteins. Ng et al (2021) expanded hBM‐MSCs on gelatin microcarriers in a spinner flask and obtained harvesting efficiencies of 93% after exposing the microcarriers to pronase for 30 min (Ng et al, 2021). Dosta et al (2020) expanded human MSCs (hMSCs) on gelatin microcarriers in a 3 L bioreactor and dissolved the microcarriers using a combination of a reducing agent called tris(2‐carboxyethyl)phosphine hydrochloride (TCEP) and 0.025% Trypsin, achieving cell viabilities greater than 90% (Dosta et al, 2020).…”
Section: Harvesting: Detachment Of Cells From Microcarriersmentioning
confidence: 99%